Addressing religious extremism through theologically informed religious education - Lovat, Terry (Journal of Religious Education, 2019)
The article will put the case for a robust theology to underpin religious education with potential to address contemporary matters in a way that genuinely informs and stimulates critical and self-reflective knowing. It will utilize a Habermasian frame of reference in constructing this argument. The article will then explore religious extremism, with focus on Islamist inspired Jihadism, as a case study that illustrates the need for theological analysis to underpin any effective addressing of the issue by religious education.